The influence of the quality of human resources (SDM) and infrastructure on government performance: influence of the quality of human resources (SDM) and infrastructure on government performance - NABILA AULIA HIDAYAH; Vero Nazwa Bauzir; Didit Darmawan (Jurnal Ecoment Global, 2025)
People today place growing expectations on the quality of public services they receive, yet the performance of government bureaucracy is still often viewed as less than optimal. Several factors contribute to this situation, particularly the limited quality of human resources and inadequate infrastructure. This study seeks to explore how human resource quality and infrastructure influence government performance. Using a literature review approach, it examines previous research from journal articles, books, and other academic publications. This method provides a broad and integrated understanding of how these two aspects human resources and infrastructure interact to shape governmental effectiveness. The review findings highlight that both human resource quality and infrastructure have a significant impact on enhancing government productivity, efficiency, and accountability. The competence, integrity, and technological capability of civil servants are key drivers of better performance, enabling them to carry out their duties effectively and respond more promptly to citizens’ needs. At the same time, sufficient and up-to-date facilities ensure smoother task execution, faster service delivery, and fewer operational barriers. Overall, the literature suggests that improving both human resource capacity and infrastructure development is fundamental to strengthening bureaucratic performance. Therefore, continuous training and infrastructure enhancement should be prioritized as core strategies in advancing public service reform. Keywords: Quality of Human Resources, Infrastructure, Government Performance, Literature